2016
DOI: 10.17795/jjhs-32114
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Epidemiology of Fatal Traffic Accidents in the Khuzestan Province

Abstract: Background: Traffic accidents with about 1.24 million deaths and 20 to 50 million cases of injury or disability per year are one of the most important public health challenges around the world. In Iran, traffic accidents, with an annual incidence of 32 cases per 100 thousand people, are considered as the second leading cause of death and the most common cause of injury. Objectives: This study aimed to evaluate the epidemiological pattern and mortality rate caused by traffic accidents during year 2012 in the Kh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
4
4
0
Order By: Relevance
“…At night, emergency personnel may not be able to take the necessary measures for the injured. Most road accidents leading to death had occurred in the spring and autumn, which was consistent with the studies in Sistan and Baluchestan, Kermanshah, and Khuzestan, Iran (22,26,27). However, this finding was not in agreement with that of the study in Zanjan and on the Iranian police data, which reported that the highest rate of deaths due to traffic accidents occurred in the summer and winter, respectively (7,23).…”
Section: Discussionsupporting
confidence: 71%
“…At night, emergency personnel may not be able to take the necessary measures for the injured. Most road accidents leading to death had occurred in the spring and autumn, which was consistent with the studies in Sistan and Baluchestan, Kermanshah, and Khuzestan, Iran (22,26,27). However, this finding was not in agreement with that of the study in Zanjan and on the Iranian police data, which reported that the highest rate of deaths due to traffic accidents occurred in the summer and winter, respectively (7,23).…”
Section: Discussionsupporting
confidence: 71%
“…This province, which is the focus of the current research, is the leader in terms of road accidents in Iran. Nearly 1300 people lose their life, and more than 15,000 people get injured or disabled in road traffic accidents in the Khuzestan province each year [12,17].Although site selection science has witnessed a great improvement in the last two decades, there are still several challenges in this topic. Many of these location selection methods are based on a fundamental analysis of experiences, or even predilection.…”
mentioning
confidence: 99%
“…RESs must be located carefully because, in an emergency, staff should be able to reach the site of the accident within 5 min [28]. Hence, considering this crucial temporal aspect, the coverage matrix is essential for describing alternative locations [23].By reviewing various studies, the significant role of pre-hospital services and emergency in a road accident has improved [17,29,30]. Early research has shown that good quality pre-hospital services have a high impact on the reduction of the death rate caused by brain trauma resulting from accidents [24,25].…”
mentioning
confidence: 99%
See 2 more Smart Citations